Rebranding the Serbian Armed Forces - Dašić Dejan (Војно дело, 2014)
The power of brands is very high, so it is important to know how they work; how they are managed; how they are created and maintained; why some are successful, and others are not. However, branding is not just about function, presence or visibility; emotional connection with people is of paramount importance for a complete success. The Serbian Armed Forces are one of the oldest brand, which has huge social significance and impact. It is a brand that is firmly rooted in the minds of people, which, despite all the tragic events of the early 1990s, arouses positive emotions. The Serbian Army lost its identity back in 1918. Since the Union of Serbia and Montenegro was dissolved, the Serbian Armed Forces have been in quest for its identity, shattered image, elements of a new name, ideas, and structures. True and strong brands are long-lived. However, in case of their neglect, carelessness and lack of commitment, they need revitalization and rebranding.